Lateral stress and its transmission law caused by operation of a double-wing subsoiler in sandy loam soil - Qin, Kuan; Zhao, Yun; Zhang, Yongzheng; Cao, Chengmao; Shen, Zhougao (Frontiers in Environmental Science, 2022)
Subsoiling improves the soil structure comprehensively through lateral disturbance, which originates from the subsoiling-induced lateral stress and its transmission process. To improve the quality of subsoiling, a series of soil bin experiments were performed to measure the subsoiling-induced lateral stress in the shallow, middle, and deep soil layers. This was achieved by burying an array of point pressure transducers in the soil bin and investigating the transmission pattern of the lateral stress. The experimental results demonstrate that the lateral stress induced by subsoiling at a lateral position varies with time. The lateral stress at almost all the positions first decreased, then increased, decreased, and then finally stabilized. The temporal variation had the characteristics of a sinusoidal curve. The analysis of the final stable lateral stress revealed that the absolute average final lateral stresses in the shallow layer is the greatest (0.1617 N), whereas it is the smallest in the middle layer (0.0733 N). This indicates that subsoiling had the greatest influence on the shallow soil layer and the smallest influence on the middle soil layer.